2020
DOI: 10.33867/jka.v7i1.166
|View full text |Cite
|
Sign up to set email alerts
|

Karakteristik Pasien Fraktur Ekstermitas Bawah

Abstract: Fraktur merupakan salah satu penyebab cacat diantaranya akibat kecelakaan. Fraktur ekstremitas bawah sering terjadi terkait dengan morbiditas yang cukup besar dan meenyebabkan perawatan panjang di rumah sakit. Gangguan akibat fraktur berdampak pada toleransi aktivitas sehingga mengurangi produktivitas. Selama ini karakteristik penderita fraktur ektermitas bawah belum diketahui, sehingga jika tidak dilakukan tidak dapat diketahui pencegahan resiko fraktur. Penelitian ini bertujuan untuk mengetahui karakteristik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 6 publications
0
7
1
4
Order By: Relevance
“…The productive age has the highest likelihood of experiencing accidents due to their high level of activities and mobilization. 4 We, however, found no association between age and quality of life and similarly for gender. This is not in accordance with research conducted by Indrayani and Ronoatmodjo S (2018) which found that the quality of life is related to gender, 10 while Hamzah (2016) stated that women have a lower quality of life compared to men because women have responsibilities for household tasks compared to men which will have an impact on health recovery.…”
Section: Original Articlecontrasting
confidence: 48%
See 3 more Smart Citations
“…The productive age has the highest likelihood of experiencing accidents due to their high level of activities and mobilization. 4 We, however, found no association between age and quality of life and similarly for gender. This is not in accordance with research conducted by Indrayani and Ronoatmodjo S (2018) which found that the quality of life is related to gender, 10 while Hamzah (2016) stated that women have a lower quality of life compared to men because women have responsibilities for household tasks compared to men which will have an impact on health recovery.…”
Section: Original Articlecontrasting
confidence: 48%
“…6 During their healing time, fracture patients often have to rely on others even for basic needs, thus this may influence their physical and social functions which belong to the quality-of-life domain. 4 Family is the main source of strength that contributes to the resilience of each family member. 7 Family support is a form of support provided by families who live at home with patients including emotional support, appreciation and information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the World Health Organization (WHO), the increase in the number of cases involving fractures can be caused by the increase in the number of vehicles. An increasing age can also be a factor in fractures due to the decreased bone mass [1,2]. One of the treatments for patients with fractures is to carry out bone implants using biomaterials [3].…”
Section: Introductionmentioning
confidence: 99%